If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 0.5(8x + -6) = 2(4x + 3) Reorder the terms: 4x + 0.5(-6 + 8x) = 2(4x + 3) 4x + (-6 * 0.5 + 8x * 0.5) = 2(4x + 3) 4x + (-3 + 4x) = 2(4x + 3) Reorder the terms: -3 + 4x + 4x = 2(4x + 3) Combine like terms: 4x + 4x = 8x -3 + 8x = 2(4x + 3) Reorder the terms: -3 + 8x = 2(3 + 4x) -3 + 8x = (3 * 2 + 4x * 2) -3 + 8x = (6 + 8x) Add '-8x' to each side of the equation. -3 + 8x + -8x = 6 + 8x + -8x Combine like terms: 8x + -8x = 0 -3 + 0 = 6 + 8x + -8x -3 = 6 + 8x + -8x Combine like terms: 8x + -8x = 0 -3 = 6 + 0 -3 = 6 Solving -3 = 6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 0=12b-12 | | -5j+-16j+13j=16 | | 12=3(-2-2) | | h^2+b^2=8.5-h^2 | | x^2+y^2=8.5-h^2 | | 2c-(-6)=12 | | 5x-1+1x+15=6+5x+14-2x | | b+9=8+7 | | -6x-6(-3x)=-24 | | 2y+11=6-y | | (3k+1)x^2+2x=1 | | 7v+2(v-2)=-22 | | t*5-7=10 | | -5(2r+4)=10 | | -9x+-20x+19x+5x-(-9x)=-12 | | -6x+4x=14 | | 6t-3t-3t+3t=18 | | x*(x+1)+109=x+(x+1) | | 16t-15t=14 | | x=y-11 | | -3x-(-8x)=15 | | (8/125)-2/3 | | 5x-1+1x+15=6+5x+14-21 | | 19t-11t=16 | | -8x-7(-6x)=0 | | y=50+15x | | 9q-3q=6 | | -5h-3-7h=-171 | | 10+5u=-21 | | 2c-4=14c-10 | | 4(y+5)-y=35 | | a+(-1.6)=-3.7 |